ANALISIS FAKTOR YANG MEMPENGARUHI PENGGUNA JASA KANTOR JASA PENILAI PUBLIK DI INDUSTRI PERBANKAN - Kholis, Nur; Andayani, Asti (Economicus, 2018)
Appraisal or Valuation is a process of work to provide estimates and opinions on the economic value of an object of valuation at a certain time in accordance with the SPI and applicable laws and regulations. Valuation is very necessary in banking management, especially to estimate the value of collateral that is used as a second way out of financing or credit which is one of the core business of banking. By the increasing of bank financing / credit needs and the number of Appraisers and Public Appraisal Service Company, competition has arisen so that a Public Appraisal Services Office selection will be held to be used in the banking industry. The method of this research is descriptive analysis and retrieval of data taken by means of interviews, surveys and direct observations and literature, which shows the results that the role of KJPP is very important and needed in banking business growth with several factors that influence service users including qualifications of Appraisers, Standard of Procedure, Service Level Agreement, active role in associations and several other things.